Academic Predictors of Mental Health Outcomes for Children and Youth with Emotional Disturbance - Callahan, John J. (2011)
Research suggests a strong correlation linking academic achievement and mental health outcomes in children with emotional disturbance (ED) (Kauffman, 2005 U.S. Department of Education, 2006). However, the exact nature of this critical relationship remains unclear. This study used a series if regression analyses and Z-Tests to investigate the predictive relationship of measures of academic achievement in determining social-emotional function over time. Examined was a sample of 261 students receiving special education and mental health services at a treatment center. Academic, mental health and demographic information was gathered from a preexisting archive. Students were assessed annually using the KTEA-II in the areas of reading, writing, and mathematics. Assessment of students' day-to-day social-emotional functioning was measured using the Ohio Scales. Results indicated that, after a year's time, the predictive value of writing achievement in determining social-emotional functioning was statistically significant and the relationship strengthened with time. Implications of the study are explore